The importance of sulphur in oilseed production – A South Asian context - V. Visha Kumari; K.A. Gopinath; M.A. Sarath Chandran; B. Sunitha; K. Sriram; M.A. Ansari; M.S. Rao; V.K. Singh (Oil Crop Science, 2025)
Sulphur (S) is essential for the quality of oilseed crops, ranking as the fourth major nutrient after nitrogen (N), phosphorus (P), and potassium (K). While crops need sulphur in slightly lower amounts than phosphorus, maintaining optimum sulphur levels is crucial for oilseed yield and quality. Factors such as sulphur dynamics, impact of deficiency, application methods, and climate change must be addressed to improve agricultural practices. In South Asian countries like India, Pakistan, and Bangladesh, oilseeds are vital to the agricultural economy, supporting food security, livelihoods, and economic growth. However, climate change, marginal land cultivation, and a shift to more profitable crops like wheat and maize have led to a decline in oilseed productivity. Sulphur is particularly important for vital plant functions, including protein synthesis, chlorophyll formation, and resistance to abiotic stress. Proper management of sulphur can significantly enhance the yield, oil content, and seed quality. Sulphur fertilization improves crop resilience to pests, diseases, and environmental stresses, resulting in healthier plants. To optimize oilseed production, best practices for sulphur management like integrated nutrient management, regular soil testing, and the strategic application of sulphur-enriched fertilizers must be adopted. Despite its significance, many South Asian soils suffer from sulphur deficiency due to inadequate replenishment and reliance on high-analysis fertilizers. By enhancing sulphur availability, oilseed producers can significantly increase crop yields, improve oil content, and promote overall plant health, contributing to the agricultural economy and food security in the region. This manuscript aims to evaluate the critical role of sulphur in enhancing the yield, oil quality, and stress resilience of oilseed crops in South Asia.